Accelerating Smart Governance Through Mandatory Cashless Parking on Public Roads in Surabaya - Kristyan Dwi Djahjono; Nur Rusydina bt Khadzali; Dandy Patrija Wirawan; Zainal Fatah; Sapto Pramono (International Journal of Social Science and Humanity, 2024)
The digital transformation within the public sector has shifted from an optional advancement to a primary parameter for local government success in managing dynamic metropolitan areas. This research examines the acceleration of Smart Governance in Surabaya through the implementation of the mandatory non-cash parking policy on public roads. Using a qualitative approach with a descriptive-analytical design, the study explores how this transition redefine the relationship between the government, parking attendants, and citizens. Findings indicate that the policy effectively minimizes budget leakage and enhances fiscal transparency. The integration of digital payment systems has transformed traditional parking management into a data-driven service, fostering public trust through accountable financial tracking. Furthermore, the shift from cash to digital transactions has successfully professionalized the role of parking attendants within the urban ecosystem. However, success relies heavily on consistent infrastructure readiness and public literacy. The study concludes that Surabaya's non-cash parking model serves as a vital instrument for strengthening Regional Original Revenue (PAD) while modernizing urban governance. These implications suggest that digital integration is not merely a technical change but a fundamental shift in bureaucratic culture. This model provides a strategic framework for other Indonesian metropolitan cities aiming to implement similar digital-based public service innovations and sustainable smart city governance.